Semantyka czeskich wykrzykników - Krzempek, Monika (Komisja Slawistyczna PAN, Oddział w Poznaniu, IFS UAM, Wydawnictwo PRO, 2015)
The aim of the paper is a semantic analysis of Czech interjections. The analysed material comes from the internet language corpora: The Czech National Corpus SYN2000, SYN2005, ORAL2008, SYN2010. The list of analysed interjections consists of automatically selected lexemes with the tag interjection in the corpus SYN2000 and of lexemes qualified as interjections in the dictionary of the standard Czech language (Slovník spisovné češtiny pro školu a veřejnost 2007). Gathered data comprise 250 lexemes (with variants). The paper consists of four chapters. The first one provides an introduction to the subject matter and includes a short summary of the views and opinions on the semantic structure of interjections. In the second chapter the author briefly describes methods and the conception of the meaning which are taken into account in the paper (cognitive semantics). The third part provides a semantic analysis of interjections. It consists of two sections; the first one is focused on the description and characteristics of central domains within which interjections are conceptualised (domains of feelings, movement, sound, scripts and abstract domains). The second section presents the analysis of the domain matrices of interjections. Finally, the author provides a summary of the research results.
Keywords: Czech language; semantics; text corpus; interjections